(untitled) (Conferencea, 2022)
The nephritic form of GN proceeds with maximum, moderate and minimal activity, the manifestations of which determine the severity of hematuria, proteinuria, arterial hypertension, edema, and impaired renal function. Several risk factors play a role in the development of the nephritic form of GN: perinatal factors, gastrointestinal diseases, giardiasis, chronic foci of infection, heredity aggravated by renal pathology or arterial hypertension, damage to the kidney tissue long before the development of GN, which is manifested by minimal urinary syndrome. A combination of various risk factors determines the severity of kidney damage. The etiological factor in the manifestation of the nephritic form of GN is most often β-hemolytic streptococcus.